Enterprise Architecture and Operational Resilience Implications of Ambient AI Scribes in Healthcare Payer Ecosystems - Abhilasha , Abad (International Journal of Health Sciences, 2026)
Purpose: This study examines how ambient AI scribes; systems that combine automated speech recognition (ASR) and large language models (LLMs), influence payer‑side enterprise architecture and operational resilience once AI‑generated clinical documentation enters claims processing ecosystems. Methodology: An enterprise architecture and systems‑level analytical approach is used to evaluate the integration of AI‑generated documentation into payer workflows. A four‑layer reference framework is proposed, covering ingestion and normalization, validation and risk scoring, claims processing integration, and observability and audit. An Operational Impact Framework (OIF) is also introduced to link AI‑generated documentation to measurable payer performance indicators. The analysis draws on payer operational datasets. Data collection utilized structured architectural analysis, metadata lineage tracing, rule‑execution monitoring, and validation heuristics. Tools and techniques were applied in accordance with APA guidelines, including systematic evaluation of coding specificity, documentation completeness, and AI confidence scoring. Findings: Normalized and validated AI‑generated documentation improves documentation structure, coding specificity, and metadata traceability. These enhancements support higher auto‑adjudication rates, lower denial rates, reduced manual review volumes, and faster root‑cause identification during production incidents, ultimately strengthening operational resilience. Unique Contribution to Theory Practice and Policy: This study shifts the focus from provider‑side workflow optimization to payer‑side enterprise architecture. It reframes ambient AI scribes as upstream inputs that reshape deterministic claims automation pipelines, data quality patterns, and operational resilience practices across large healthcare IT ecosystems. The research provides a structured blueprint for integrating ambient AI documentation into payer systems while maintaining compliance, auditability, and operational reliability. A Responsible AI governance model is proposed to support explainability, bias mitigation, hallucination detection, and regulatory audit readiness.